IMPACT OF FOLIC ACID ON THE NEUROTRANSMITTERS AND OXIDANT ANTIOXIDANTBALANCE IN HYPOTHYROID AND HYPERTHYROID RATS - HEBA BARAKAT,; SHIMAA EL-MASRY, (International Journal of Pharma and Bio Sciences, 2015)
Thyroid hormones status plays an important role in various body activities. Thus, this study aimed to clarify the effect of hypothyroidism and hyperthyroidism in rats on the serum neurotransmitters, oxidative stress, total homocysteine and antioxidant defense system in relation to folic administration. The adult male rats were administered carbimazole and eltroxin to induce hypo and hyperthyroidism, respectively. In hypothyroid group, a marked depletion was observed in serum free thyroxine and free triiodothyronine with a significant increase in the thyroid stimulating hormone levels. The reverse pattern was recorded in hyperthyroid group. All of these variations were modulated by folic acid. The neurotransmitters were greatly disturbed; however folic acid administration exerted beneficial effects. In both of the thyroid statuses, serum oxidative stress markers were increased but glutathione reductase was inhibited. Folic acid administration lowered the serum total homocysteine level in both of the hypothyroid and hyperthyroid.